Factors Affecting the Working Time of Female Crystal Guava Farm Woman Laborers in Gadingrejo Village, Umbulsari Subdistrict, Jember Regency - Prakoso, Gray Aji; Hadi, Syamsul; Aulia, Anisa Nurina (International Applied Science, 2024)
Jember Regency has high potential in developing horticultural crop cultivation, especially fruit crops. One of the fruit commodities in Jember Regency is crystal guava. In crystal guava farming activities require labor, where labor is divided into two, namely male labor and female labor. Farming activities carried out by farm laborers are influenced by the outflow of work time. The purpose of this study was to analyze the factors that influence the work time of female crystal guava farm laborers in Gadingrejo Village, Umbulsari District, Jember Regency. The results showed that the factors that were significant in influencing the labor time of female crystal guava farm laborers in Gadingrejo Village, Umbulsari District, Jember Regency were age (X1) and education level (X2) while the factors that were not significant were work experience (X3), number of family members (X4) and husband's income (X5).